Strength and Weathering of Rock As Boundary Layer Problems. (World Scientific, 2001)
A discussion of the concepts, definition and experience of strength, particularly rock strength, with application of experimental techniques. It addresses the physical-chemical aspects of the strength of pure phases, strengthening of grain packings by "intramolecular forces", and more.